Progranulin mutations result in impaired processing of prosaposin and reduced glucocerebrosidase activity - Valdez, Clarissa (Hum Mol Genet, 2020)
Frontotemporal dementia (FTD) is a common neurogenerative disorder characterized by progressive degeneration in the frontal and temporal lobes. Heterozygous mutations in the gene encoding progranulin (PGRN) are a common genetic cause of FTD. Recently, PGRN has emerged as an important regulator of lysosomal function. Here, we examine the impact of PGRN mutations on the processing of full-length prosaposin to individual saposins, which are critical regulators of lysosomal sphingolipid metabolism. Using FTD-PGRN patient-derived cortical neurons differentiated from induced pluripotent stem cells, as well as post-mortem tissue from patients with FTLD-PGRN, we show that PGRN haploinsufficiency results in impaired processing of prosaposin to saposin C, a critical activator of the lysosomal enzyme glucocerebrosidase (GCase). Additionally, we found that PGRN mutant neurons had reduced lysosomal GCase activity, lipid accumulation and increased insoluble α-synuclein relative to isogenic controls. Importantly, reduced GCase activity in PGRN mutant neurons is rescued by treatment with saposin C. Together, these findings suggest that reduced GCase activity due to impaired processing of prosaposin may contribute to pathogenesis of FTD resulting from PGRN mutations.